Estimation Of Ki-67 Positivity In Relation To Size Of Tumor And Age OfPatient In Invasive Breast Carcinoma - M Mohiuddin Alamgir; Saeeda Baig (ziauddin University, 2024)
ABSTRACT Background: Identification of cells in the replicative pool for cases of breast cancers and their association with various conventional prognostic parameters would have widespread predictive as well as therapeutic value. Cell proliferation studies would supplement existing markers for devising appropriate treatment protocol for individual cancer cases. Objective: To evaluate proliferative activity via Ki-67 immunohistochemical labeling in invasive breast carcinoma and to find its relationship to age of the patient and size of tumor aithe time of diagnosis. Materials & methods: This Descriptive Study was carried out at Department of Pathology, Basic Medical Sciences Institute, JPMC, Karachi, Pakistan, Formalin-fixed-paraffin-embedded tissues of 50 cases of diagnosed invasive lobular carcinoma (ILC) and invasive ductal carcinoma (IDC) with and without lymph node involvement were retrieved. Immunohistochemical staining for Ki-67 antigen was performed. The numberof positively stained nuclei in 1000 tumor cells in at least five representative high power fields was counted. "EPI-INFOR" wasusedforstatistical analysis. Results: 33 cases showedpositive nuclear staining for Ki-67 antigen with 08 ILC cases and 25 IDC cases, respectively. In pre-menopausal women, positive nuclear staining was observed in 04/08 ILC cases and 15/25 cases of IDC with a Ki67 positivity of 11.543.8% and 15.9411.5%, respectively. In postmenopausal women, 04 ILC cases and 10 IDC cases showed nuclear staining with 15+6.9% and 16+7.1% Ki-67 positivity, respectively. Tumor size of < 2 cm was observed in 03 cases of ILC and 07 of IDC with 13.9 + 0.4% and 13.9 + 0.4% Ki-67 positivity, respectively. Tumors of 2.1 to 5.0 cm in size were present in 02 cases of ILC and 07 cases of IDC with 10.9 + 3.2% and 14.04 + 5.34% Ki-67 positivity, respectively. Tumors = 5.1cm were seen in 03 cases of ILC and 11 cases of IDC with 14.2 + 9.3% and 17.38 + 11.30% Ki67 positivity, respectively. The results were notstatistically significant. Conclusion: Ki-67 positivity showed a tendencyto increase with increasing size of the tumor in breast cancers. Since the results of pre and post menopausal patients were similar, hence response to cytotoxic chemotherapyis anticipated to be equivocal in them. KEY WORDS:Ki-67 Positivity Index, Immunostaining, Cytotoxic Chemotherapy.